Nitric Oxide Signals Through IRAG to Inhibit TRPM4 Channels and Dilate Cerebral Arteries. Issue 6 (9th October 2021) - Ali, Sher; Solano, Alfredo Sanchez; Gonzales, Albert L; Thakore, Pratish; Krishnan, Vivek; Yamasaki, Evan; Earley, Scott
Abstract: Nitric oxide (NO) relaxes vascular smooth muscle cells (SMCs) and dilates blood vessels by increasing intracellular levels of cyclic guanosine monophosphate (cGMP), which stimulates the activity of cGMP-dependent protein kinase (PKG). However, the vasodilator mechanisms downstream of PKG remain incompletely understood. Here, we found that transient receptor potential melastatin 4 (TRPM4) cation channels, which are activated by Ca 2+ released from the sarcoplasmic reticulum (SR) through inositol triphosphate receptors (IP3 Rs) under native conditions, are essential for SMC membrane depolarization and vasoconstriction. We hypothesized that signaling via the NO/cGMP/PKG pathway causes vasodilation by inhibiting TRPM4. We found that TRPM4 currents activated by stretching the plasma membrane or directly activating IP3 Rs were suppressed by exogenous NO or a membrane-permeable cGMP analog, the latter of which also impaired IP3 R-mediated release of Ca 2+ from the SR. The effects of NO on TRPM4 activity were blocked by inhibition of soluble guanylyl cyclase or PKG. Notably, upon phosphorylation by PKG, IRAG (IP3 R-associated PKG substrate) inhibited IP3 R-mediated Ca 2+ release, and knockdown of IRAG expression diminished NO-mediated inhibition of TRPM4 activity and vasodilation. Using superresolution microscopy, we found that IRAG, PKG, and IP3 Rs form a nanoscale signaling complex on the SR of SMCs. We conclude that NO/cGMP/PKG signaling through IRAG inhibits IP3 R-dependent activation of TRPM4 channels in SMCs to dilate arteries. Significance Statement: Nitric oxide is a gaseous vasodilator produced by endothelial cells that is essential for cardiovascular function. Although NO-mediated signaling pathways have been intensively studied, the mechanisms by which they relax SMCs to dilate blood vessels remain incompletely understood. In this study, we show that NO causes vasodilation by inhibiting the activity of Ca 2+ -dependent TRPM4 cation channels. Probing further, we found that NO does not act directly on TRPM4 but instead initiates a signaling cascade that inhibits its activation by blocking the release of Ca 2+ from the SR. Thus, our findings reveal the essential molecular pathways of NO-induced vasodilation—a fundamental unresolved concept in cardiovascular physiology. Graphical Abstract: